DEVELOPMENT AND OPTIMIZATION OF MICROCRYSTALLINE CELLULOSE AND HYDROXYAPATITE MODIFIED CARBON ELECTRODE FOR VOLTAMMETRIC ANALYSIS OF PLUMBUM AND CADMIUM IONS - ALMUSTAPHA, SAKTNATU (2014)
Development of robust and in situ detection of heavy metal ions has become an important overall Green strategy. However, expensive cost, unavailability of elaborate equipments, maintenance, sample pre-treatment, and huge concentrations of solutions limit applications of some techniques such as Atomic Absoprtion spectrometry. Chemically-modified carbon electrodes (CME) are seen as low-cost and practical replacement method for the detection of such metals. This involves adjusting the chemical nature on the electrode surface by adding a modifying agent. The electrode therefore assumes the desired properties of the modifier in binding metals for enhanced selectivity, sensitivity and overall stability. Cellulose is abundantly available, natural, renewable, and biodegradable polymer which can be used as a nano-reinforcing element.